A comparison between volume and electronic concentration effects in Ce transformations - Sereni, J.G. (1994)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina